Bend loss fiber optics design based on sinusoidal and ellipse configurations - Mohd Arif, Noor Azie Azura; Burhanuddin, Dilla Durhya; Shaari, Sahbudin; Ehsan, Abang Annuar (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
Bending losses in optical fibers comprise one of the extrinsic attenuations that contribute to opticalloss and they are essential for optical fiber bending sensor applications. This work investigatedthe optical loss in a standard single-mode step-index fiber optics due to fiber bending at 1550 nmwavelength. Variations in macro-bending loss with curvature radius and turn number have beenmeasured. Curvature radius and turn number are examined for sinusoidal and elliptical shapedbending configurations. It has been found that the loss increases as the bending radius and numberof turns increase. The result also showed that elliptical shaped bending configuration producedmore loss in contrast to that of sinusoidal shaped at bending angles of 180° and 360°. The studyon the macro-bending loss in terms of curvature radius and turn number for both elliptical and sinusoidal shaped bending configurations is beneficial for future fiber optic sensor applications
Optica Applicata, Vol. 51, 2021, nr 3, s. 309-320
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; sinusoidal shape; ellipse shape; bending loss; number of turns; curvature radius